Senam Menurunkan Risiko Kejadian Jatuh Pada Lansia - Siti Munawaroh; Muhammad Raditia Septian; Desy Kurniawati Tandiyo (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2022)
Fall is one of the most case that occur on elderly. Exercise such as elderly gymnastic can overcome the problem of falling in elderly. It can increase flexibility, muscle strength, balance, and also reduce the risk of falls and injury. There needs to be a study of the eldery gymnastic correaltion with the risk of falls. This study aims to determine the correlation between elderly gymnastics with risk of falls based on DGI. Methods: This study was an analytic observational study with cross sectional approach. Sample was taken by purposive sampling. Samples were taken by 30 respondents that consist of 15 respondents join gymnastic elderly and 15 respondenst didn't join gymnastic elderly program. Respondents assessed the risk of falling by the DGI. Data were analyzed using Chi Square test, Fisher absolute test and Relative Risk (RR) measurement. Results: The result showed the value of p = 0.003 with a RR of 0.2, which showed significant research as p <0.05. Most respondents at the age of 60-74 years old and most were male. Conclusions:Elderly Gymnastic will reduce the risk of falls in elderly.